A Studi Kasus: Indigesti Sederhana pada Sapi Limousin di KUD Karya Bhakti, Ngancar, Kediri: Studi Kasus: Indigesti Sederhana pada Sapi Limousin di KUD Karya Bhakti, Ngancar, Kediri - Ningsih, Awalul Fitria; Kurnianto, Ady (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2024)
Indigestion is a syndrome of indigestion originating from the rumen or reticulum, characterized by decreased or lost movement of the rumen, weak tone of the two stomachs, indesgeta buried in it and accompanied by constipation. An indigestive case in a limousine cow named Beno, male, 12 months old, 400 kg body weight, brown hair color, was physically examined by inspection and palpation. The results of the physical examination by inspection were weakness and lethargy, hypersalivation, hyperlacrimation, slightly reddish conjunctiva of the eyes, slightly pale mucous membranes of the mouth, nose and ears and the earlobes felt cold, no lesions on the skin and hair, no lice, slightly dull hair. The results of palpation of the lymph nodes did not experience swelling. Palpation of the left abdomen was distended (the ventral part of the rumen/left paralumbar fossa felt tense, rumen movement was slow), a small amount of feces was found and the consistency was slightly runny, the frequency of urine was small. Normal body temperature is 41.1oC, abnormal respiratory rate is 49/minute. Treatment is in the form of drug therapy including injection of analgesics and antipyretics, anti-inflammatories, antihistamines, antibiotics, and multivitamins. Keywords: Simple indigestion, cow, inspection, palpation.